Pembebasan Benih Kacang Panjang (Vigna sinensis L) dari Infeksi Bean Common Mosaic Virus (BCMV) melalui Perlakuan Dry Heat - HERRY KUSUMA YUDHA; GST NGURAH ALIT SUSANTA WIRYA; I GUSTI NGURAH RAKA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
This study are aims to determine the effect of dry heat treatment (DHT) on the quality of seed beans and to determine the length of time required for dry heat treatment (DHT) in seed beans. This research has six activities, that are: 1. sampling symptomatic plants virus on long bean; 2. preparation of seed; 3. dry heat treatment (DHT); 4. test for Immunosobent Serology Enzyme-linked Assay (ELISA); 5. observations; 6. data analysis. The research were designed by completely randomized design (CRD) with six treatments and five replications. The research result show that dry heat treatment does not give adverse effects on seed germination of beans. Treatment of dry heat on a temperature of 70ºC for 60 hours most effective for inactivation of bean common mosaic virus (BCMV) on the seed beans and did not cause damage on the other elements of seed quality. Based on these studies further research on dry heat treatment to determine their effectiveness to protec plants from bean common mosaic virus (BCMV) in endemic areas, should be conducted.